Is the RSGC4 (Alicante 8) Cluster a Real Star Cluster? Peculiar Radial Velocities of Red Supergiant Stars - Sang-Hyun Chun; GyuChul Myeong; Jae-Joon Lee; Heeyoung Oh (The Astronomical Journal, 2024)
Young massive star clusters, like the six red supergiant clusters in the Scutum complex, provide valuable insights into star formation and galaxy structures. We investigated the high-resolution near-infrared spectra of 60 RSG candidates in these clusters using the Immersion Grating Infrared Spectrograph. Among the candidates in RSGC4, we found significant scattering in radial velocity (−64 to 115 km s ^−1 ), unlike other clusters with velocities of ∼100 km s ^−1 . Most candidates in RSGC4 have Q _GK _s values larger than 1.7, suggesting that they could be early AGB stars. Four candidates in RSGC4 exhibit infrared excess and distinct absorption features absent in other candidates. Two of these stars exhibit absorption lines resembling those of D-type symbiotic stars, showing radial velocity changes in multiepoch observations. Analysis of relative proper motions revealed no runaway/walkaway stars in RSGC4. The dynamic properties of RSGC4 and RSGC1 differ from the disklike motions of other clusters: RSGC4 has low normalized horizontal action J _hor = J _ϕ / J _tot and vertical action J _ver = ( J _z − J _R )/ J _tot values and high eccentricities, while RSGC1 has vertical motions with high J _ver values and inclinations. We propose that RSGC4 may not be a genuine star cluster but rather a composite of RSGs and AGB stars distributed along the line of sight at similar distances, possibly originating from various environments. Our results suggest a complex and hierarchical secular evolution of star clusters in the Scutum complex, emphasizing the importance of considering factors beyond density crowding when identifying star clusters in the bulge regions.